2020
DOI: 10.3390/microorganisms8020286
|View full text |Cite
|
Sign up to set email alerts
|

pH and Phosphate Induced Shifts in Carbon Flow and Microbial Community during Thermophilic Anaerobic Digestion

Abstract: pH is a central environmental factor influencing CH4 production from organic substrates, as every member of the complex microbial community has specific pH requirements. Here, we show how varying pH conditions (5.0–8.5, phosphate buffered) and the application of a phosphate buffer per se induce shifts in the microbial community composition and the carbon flow during nine weeks of thermophilic batch digestion. Beside monitoring the methane production as well as volatile fatty acid concentrations, amplicon seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 112 publications
1
3
0
Order By: Relevance
“…Similar to our work, the results demonstrated that there were significant retarding effects on CH 4 production; the reactors with 1000 and 2000 mg/L PO 4 –P produced nearly the same amount of CH 4 as the control reactor but after 46 and 71 days, respectively . Others proved that addition of P-buffer (≥20 mM) to AD reactors specifically inhibited acetoclastic methanogenesis. , A delayed initiation of methanogenesis was due to the adaptation time needed by hydrogenotrophic methanogens . The PO 4 –P concentration in 100 mM PBS medium is approximately 3000 mg/L, and this explains the lowest CH 4 production and extended delay in the AD-no-GAC reactors.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to our work, the results demonstrated that there were significant retarding effects on CH 4 production; the reactors with 1000 and 2000 mg/L PO 4 –P produced nearly the same amount of CH 4 as the control reactor but after 46 and 71 days, respectively . Others proved that addition of P-buffer (≥20 mM) to AD reactors specifically inhibited acetoclastic methanogenesis. , A delayed initiation of methanogenesis was due to the adaptation time needed by hydrogenotrophic methanogens . The PO 4 –P concentration in 100 mM PBS medium is approximately 3000 mg/L, and this explains the lowest CH 4 production and extended delay in the AD-no-GAC reactors.…”
Section: Resultssupporting
confidence: 87%
“…31 Others proved that addition of P-buffer (≥20 mM) to AD reactors specifically inhibited acetoclastic methanogenesis. 32,33 A delayed initiation of methanogenesis was due to the adaptation time needed by hydrogenotrophic methanogens. 33 The PO 4 −P concentration in 100 mM PBS medium is approximately 3000 mg/L, and this explains the lowest CH 4 production and extended delay in the AD-no-GAC reactors.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular and ongoing monitoring of pH levels is crucial to promptly identify any deviations and implement necessary corrective measures. Ensuring an adequate buffering capacity in the digester can assist in reducing pH fluctuations [90]. The inclusion of buffering agents such as bicarbonates can help maintain stable pH levels.…”
Section: Correlation Between Nutrients and Biogas Compositionmentioning
confidence: 99%